Particle and Nuclear Physics at J-PARC - Sato, Takahiro; Takahashi, Toshiyuki; Yoshimura, Koji (Lecture Notes in Physics, 2009)
With the imminent operational start of the Japan Proton Accelerator Research Complex (J-PARC), a range of fundamental experiments in nuclear and particle physics will come within reach in the near future, while this new facility will also provide a pulsed neutron source for applications in materials and life sciences. The present volume is dedicated the detailed presentation of eight among the most promising fundamental experiments, including the study of rare kaon decays (CP and T violations), neutrino oscillations, pentaquarks, hypernuclei precision spectroscopy, muon sciences (g-2, electric dipole moment, flavour violations) and meson studies (mass modification of vector mesons in medium, bound states in nuclei). This collection of surveys by leading researchers in the field primarily addresses the many postgraduate students and nonspecialists from related areas entering this research over the next few years - they will find this volume an excellent introduction to both the physics and the particular experiments that will be conducted at J-PARC.